BUDD−CHIARI SYNDROME IN A PATIENT WITH SMALL CELL LUNG CANCER: A CASE REPORT - Bjelakovic, Marko; Radović, Milan; Stamenković, Zoran; Bjelaković, Milica; Jović, Kristina (Acta medicae Medianae, 2025)
Budd−Chiari syndrome (BCS) is a rare disease caused by hepatic venous outflow tract obstruction which can occur anywhere along the path from the hepatic venules to the inferior vena cava inflow into the right ventricle. Liver congestion results in hypoxic damage of hepatocytes. Etiologic factors related to BCS are hematologic and malignant disease. Budd−Chiari syndrome is a rare condition in lung cancer patients. Only a few cases have been reported during the last decades. We present a very rare case of acute BCS syndrome in a patient with primary small cell lung cancer caused by tumor thrombus of the inferior vena cava. The diagnosis was made based on ultrasound findings. Thereafter treatment with anticoagulant therapy was started. Due to the poor performance status and significant liver damage, specific oncological treatment with chemotherapy was not started. The patient was discharged from the hospital and advised to continue symptomatic therapy. Pulmonologists should be aware that BCS syndrome could be a presenting feature of an unrecognized lung cancer.
Keywords: Budd−Chiari syndrome, lung cancer